2022
DOI: 10.12659/ajcr.938476
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Associated Bullous Pemphigoid in a Hemodialysis Patient After Kidney Transplant Failure

Abstract: Objective:Rare disease Background:Patients with end-stage renal disease (ESRD) who require dialysis can develop a variety of skin conditions, such as pruritus, xerosis, skin infections, and autoimmune reactions. Bullous pemphigoid (BP) is an autoimmune bullous disorder with an increasing incidence. It can be caused by over 90 medications, but levofloxacin-induced BP in hemodialysis patients has not yet been reported. This report is of a 27-year-old woman with ESRD on hemodialysis who developed BP after levoflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…presented several BP cases in patients receiving peritoneal dialysis (PD), suggesting a potential correlation between the dialysis process and the onset of BP ( 6 ). This relationship was further supported by J Miao et al., who reported a patient on hemodialysis had levofloxacin-induced BP, indicating the potential role of certain medications in triggering BP among patients with ESKD ( 7 ). A nationwide population-based cohort study revealed that the hazard ratio (HR) for BP in patients with ESKD was 2.12 compared to individuals without chronic kidney disease (CKD) ( 8 ).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…presented several BP cases in patients receiving peritoneal dialysis (PD), suggesting a potential correlation between the dialysis process and the onset of BP ( 6 ). This relationship was further supported by J Miao et al., who reported a patient on hemodialysis had levofloxacin-induced BP, indicating the potential role of certain medications in triggering BP among patients with ESKD ( 7 ). A nationwide population-based cohort study revealed that the hazard ratio (HR) for BP in patients with ESKD was 2.12 compared to individuals without chronic kidney disease (CKD) ( 8 ).…”
Section: Introductionmentioning
confidence: 70%
“…Two BP cases were induced by mammalian target of rapamycin (mTOR) inhibitors, as evidenced by immediate resolution upon drug discontinuation followed by relapse after rechallenge ( 46 ). Other agents, such as cefixime and levofloxacin, were also considered to induce pemphigoid diseases in patients with ESKD ( 7 , 47 ). Mechanisms of drug-induced pemphigoid diseases included the possibility that certain drugs could change the structure of autoantigens, expose previously sequestered autoantigens, promote autoantibodies production by acting as antigenic haptens, disrupt the DEJ directly, and cause cross-reaction of the immune response ( 7 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…The medications include DPP-4i, antibiotics, NSAIDs, beta-blockers, diuretics, TNF-α, and immune checkpoint inhibitors targeting programmed cell death receptor 1 (PD-1) and its ligand (PD-L1). 6,25 The main components of bullous pemphigoid pathophysiology are immunologic and inflammatory. 5 Bullous pemphigoid autoantibodies primarily target BP180 and BP230, hemidesmosomal proteins of dermo-epidermal junction.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnoses were typically determined by the authors of the case reports. For example, in a case report titled “Levofloxacin-Associated Bullous Pemphigoid in a Hemodialysis Patient After Kidney Transplant Failure” [ 33 ] we extracted from “A 27-year-old female with hemodialysis was admitted for evaluation of a worsening bullous rash and shortness of breath over the last 3 days...” to “...Although the swab PCR test for VZV and HSV was negative, there was still concern about disseminated herpes zoster, as the patient was immunosuppressed” as a case description. Additionally, the final diagnosis was levofloxacin-associated bullous pemphigoid.…”
Section: Methodsmentioning
confidence: 99%